2009
DOI: 10.1007/s00270-009-9765-6
|View full text |Cite
|
Sign up to set email alerts
|

Angioplasty or Primary Stenting for Infrapopliteal Lesions: Results of a Prospective Randomized Trial

Abstract: Excellent results with small stents in coronary arteries have led endovascular therapists to their use in infrapopliteal vessels. However, to date no level I evidence exists to recommend primary stenting over infrapopliteal angioplasty alone. The aim of this randomized single-center trial was to compare their 1-year outcome. A total of 38 limbs in 35 patients with critical limb ischemia were randomized to angioplasty (22 pts) or primary stenting (16 pts). Target lesions were infrapopliteal occluded (36) or ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 34 publications
1
54
0
5
Order By: Relevance
“…Les auteurs concluent donc que l'angioplastie-stenting a une place pour l'angioplastie infrapoplitée si la procédure est compliquée d'une dissection ou d'un échec mais pas en première intention [52][53][54].…”
Section: Angioplastie Par Voie Rétrogradeunclassified
“…Les auteurs concluent donc que l'angioplastie-stenting a une place pour l'angioplastie infrapoplitée si la procédure est compliquée d'une dissection ou d'un échec mais pas en première intention [52][53][54].…”
Section: Angioplastie Par Voie Rétrogradeunclassified
“…Studies by others have demonstrated similar results. 97,98 Thus, DES seems to offer less repeat revascularization compared with BMS and possibly less amputation, but the value of its routine use compared with balloon angioplasty is less certain. Ongoing and future trials will hopefully clarify the clinical efficacy and cost-effectiveness of DES for this indication.…”
Section: Infrapopliteal Balloon Angioplasty For CLImentioning
confidence: 99%
“…Clinical data suggested that BMS had little clinical advantage over successful balloon angioplasty in patients with CLI. 76,77) As DES platforms became established in the coronary bed, this encouraged acquisition of preliminary infrapopliteal data regarding primary DES. 78,79) These data…”
Section: Drug-eluting Stentsmentioning
confidence: 99%